SALES AND BILLING APPLICATIONS RECEIVABLES - Erni Kustini (Jurnal Sistem Informasi, 2010)
Scientific writing is about an application program of Sales and BillingReceivables, application is made to facilitate the recording of sales andcollection of accounts receivable. And to help present a report on thetransaction, is also useful and help some suppliers, customers, sales, and store inthe transaction. In this paper the author only uses fictitious data because theauthor wants to build an application Panagihan Sales and receivables of ageneral nature that can be customized with a company that wants to build thisapplication program.